Features of childhood cancer in primary care: a population-based nested case-control study. (24th May 2012) - Dommett, RM; Redaniel, TR; Stevens, MCG; Hamilton, W; Martin, RM
Abstract : Background: Cancer in children is rare and provides a major diagnostic challenge to clinicians in tertiary, secondary and primary care. Delayed diagnosis may worsen survival; at the very least it reduces the confidence of patients and parents in their doctor. This study investigated the risk of cancer in children with the alert symptoms identified in current UK guidance (NICE 2005), or with increased consultation frequency in primary care. Methods: A population-based, nested case-control study used data from the General Practice Research Database (GPRD). 1267 children age 0-14 years diagnosed with childhood cancer were matched to 15318 controls. Likelihood ratios (LR) and positive predictive values (PPVs) were calculated to assess the risk of cancer based on symptoms and consultation patterns. Results: In the 12 months and 3 months before diagnosis, 33.7% and 27.0% of cases, respectively, had a recorded alert symptom compared to 5.4% and 1.4% of controls. The positive predictive value of having cancer for any alert symptom in the 3 months before diagnosis was 0.12% and in the 12 month period was 0.09%. Primary care consultation rates in the year before diagnosis were higher in cases than controls, particularly in the 3 months before diagnosis when 86% of cases consulted their GP compared to 41% of controls. Of these, 36% of cases had consulted 4 times or more compared to 9% of controls. The PPV for cancer in a child consulting 4 times or more in 3 months was 0.01%. Conclusion: Alert symptoms and a pattern of frequent consultations in a short period of time are associated with childhood cancer. Individual symptoms and consultation patterns have very low positive predictive values for cancer in primary care (e.g. of 10, 000 children with a recorded alert symptom, only 12 would be diagnosed with cancer within 3 months) however their presence changes the pre-test probability of cancer from around 1 in 10, 000 to 1 in 1, 000. Future studies to further define the symptoms of cancer in children presenting in primary care are required. This work has implications for ways to approach concerns regarding perceived delays in diagnosis.